The Total Pectoralis Major Muscle Myocutaneous Free Flap - Hallock, Geoffrey G. (Journal of Reconstructive Microsurgery, 2013)
Even though the pectoralis major muscle has many similarities to the latissimus dorsi muscle, only the latter has a reputation as a “workhorse” free flap. Nevertheless, the former in special circumstances can provide a muscle flap of comparable surface area when used in its totality along with a skin paddle, with a consistent pedicle of large caliber, that causes minimal functional disturbance. However, the pedicle is very short, and vein grafts may be necessary to reach any recipient site. Nevertheless, the total pectoralis major muscle myocutaneous flap may be the largest free flap available when the patient must be kept in a supine position and no perforator flaps are reasonably available.
Keywords: pectoralis major muscle free flap; microsurgery